Design and evaluation of a creation of the demand model in order to increase voluntary medical male circumcision among adults in a South African community - (:unkn) unknown (My University, 2017)
Three randomized controlled trials showed the protective role of circumcision in heterosexual HIV transmission. The World Health Organization (WHO) and the Joint United Nations Program on AIDS (UNAIDS) recommend that voluntary male medical circumcision (VMMC) programs should be rolled-out wherever there is a generalized HIV epidemic and few men are circumcised. WHO recommends a prevalence rate of at least 80% male circumcision in adults to have a substantial impact on the HIV/AIDS epidemic in Eastern and Southern Africa. Starting in 2007 in the fourteen Southern and Eastern Africa countries identified as priority countries, the programs to promote the CVME have allowed a rapid increase of the male circumcision prevalence rate. So very low in 2008, it rose to about 50% in 2011. This study showed that the male circumcision prevalence has remained almost stable among adults in the township of Orange Farm since 2011. Township where a similar promotion program to other Southern and Eastern African countries is underway since 2007. We then designed and tested an innovative strategy combining the existing strategy with the elements of interpersonal communication with a financial compensation and discussions with all members of the household. This new strategy tested showed that a male circumcision prevalence rate of 80% could be obtained in a very short time. This easily reproducible method should be encouraged in order to increase the male circumcision prevalence rate to 80% as recommended by WHO in severely HIV affected countries, and thus to decrease HIV incidence.
Keywords: African Research